EFFECT OF DIFFERENT INTERVAL SPEED TRAINING ON ATHLETE REACTION - Chen,Hongqiang (2022)
ABSTRACT Introduction: High-intensity Intermittent Training (HIIT) ranked first in the ACSM “2013 Global Training Methodology Survey”. Objective: To explore the influence of different speed training intervals on athlete reaction speed. Methods: Sixteen male bicycle athletes were randomly divided into two groups. The two groups then completed a six-week training routine (NT). The two groups then completed a six-week training routine , started 6 weeks of Sprint Interval Training (SIT) (a total of 12 lessons), with SIT instead of Normal Training (NT) live endurance training, and another training remains unchanged. Results: After 6 weeks of NT, Pmax GXT in the CG and DG groups decreased by 0.7% and 1.7%, respectively,as compared to the pre-training numbers. The difference was not statistically significant (P>0.05). And after 6 weeks of SIT, Pmax GXT increased significantly (P<0.05) in both experimental groupss,with increases of 9.2% and 10.2% for the CG and DG groups, respectively. Conclusions: The results show that intermittent training can effectively improve the aerobic metabolism of short-haul cyclists. As the power bicycle load and the training intensity and volume of the deceleration intermittent training program increase, the more significant the changes in aerobic capacity that can result in adaptability. Level of evidence II; Therapeutic studies - investigation of treatment results.